Pediatric Sand Aspiration Managed Using Bronchoscopy and Extracorporeal Membrane Oxygenation - Khaled Baqais; Meagan Mahoney; Kathleen Tobler; Anita Hui; Mary Noseworthy (Canadian Respiratory Journal)
Sand aspiration is a rare but potentially fatal occurrence to consider in near-drownings, accidental burials or cave-ins. Optimal management is not well defined.